Oenopia shirkuhensis sp. nov. (Coleoptera, Coccinellidae) from Iran mimicking Adalia bipunctata - Khormizi, Mehdi Zare; Nedvěd, Oldřich (Pensoft Publishers, 2020)
Oenopia shirkuhensis sp. nov. (Coleoptera, Coccinellidae) is described and illustrated. It was found in the mountains around Shirkooh mountain, Yazd province, and in the Kukhbenan Mountains, Kerman province, Iran. It is similar to a common ladybird Adalia bipunctata by the colour pattern on elytra. Congeneric species occurring in Iran, O. conglobata and partly O. oncina are illustrated for comparison, and an identification key is provided.
Keywords: ladybug; Mullerian mimicry; new species